If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 9 + 3 = 7 + x + 2 Reorder the terms: 9 + 3 + -2x = 7 + x + 2 Combine like terms: 9 + 3 = 12 12 + -2x = 7 + x + 2 Reorder the terms: 12 + -2x = 7 + 2 + x Combine like terms: 7 + 2 = 9 12 + -2x = 9 + x Solving 12 + -2x = 9 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 12 + -2x + -1x = 9 + x + -1x Combine like terms: -2x + -1x = -3x 12 + -3x = 9 + x + -1x Combine like terms: x + -1x = 0 12 + -3x = 9 + 0 12 + -3x = 9 Add '-12' to each side of the equation. 12 + -12 + -3x = 9 + -12 Combine like terms: 12 + -12 = 0 0 + -3x = 9 + -12 -3x = 9 + -12 Combine like terms: 9 + -12 = -3 -3x = -3 Divide each side by '-3'. x = 1 Simplifying x = 1
| 6x-3+10x-2= | | 28+19m=35+12m | | 13z+9=7z-21 | | 15+3y=7y-1 | | 7x-4=20-5x | | (100-q)/2=1250 | | 6-3m=16+2m | | 5x-(2-x)=22 | | 150m-75m+48000=50000-175m | | 3(n+.333)=2 | | 200m-125m+47750=50500+175m | | 3x^2+23x-6.5=0 | | 3x+6=2x+34 | | 3+6x=11+8x | | 2x+44=3y-9 | | 45=3(2x+7) | | m+2m+7m=60-5m | | 3+5x=10+3x | | 10v+23=93 | | 2x^2+64x+512=0 | | 7(d-5)+6= | | 2x^2+512=0 | | 3x-y(x+10)=9 | | z^2+2(1-i)z+2i=0 | | =1+3x | | x-6.1=5.3 | | 3x^5-14x^3-5x=0 | | -5k+2.7+2.4k+2.1k-5= | | 7x+4=19+2x | | h=24 | | 4x-(5x+5)=5x-47 | | y+1=-y+3 |